ANALISIS PELUANG PASAR PENJUALAN PELUMAS PERTAMINA ENDURO PADA PT. NATIOTAMA PUSAKA CONTRANDA DI KOTA PEKANBARU - Zulhendrawan '; Jushermi '; Tengku Firli Musfar (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2014)
The research was conducted at PT. Natiotama Heritage Contranda in Pekanbaru. This study took place in August 2013 until March 2014. Purpose of this study is to analyze market opportunities Enduro Pertamina Lubricants marketed by PT. Natiotama Heritage Contranda in Pekanbaru and to investigate alternative marketing policies that can be done by the company to expand market opportunities.Information retrieval is done by conducting interviews with the parties concerned as well as the analysis of secondary data submitted by the company. Then the results were analyzed using by calculating the Potential, Market Forecasts, and Market Opportunity Sales Potential ditambulasi and then described its correlation with the theories that support the discussion. Based on the analysis, it can be concluded that the results of the calculation of the potential market, market forecast, and forecast potential sales opportunities Sales knowable Enduro Pertamina Lubricants sales market is quite large and has increased every year. It required the selection of a proper marketing strategy in order to reap optimum market opportunities.Keywords: Market Potential, Market Forecasts, Sales Potential, Divination Sales, Market Opportunities and Marketing Strategies.